A companion to the Achaemenid Persian empire: Volume I & II - Jacobs, Bruno; Rollinger, Robert (Wiley Blackwell, 2021)
A Companion to the Achaemenid Persian Empire. Front Matter -- INTRODUCTION / Bruno Jacobs, Robert Rollinger -- Geography and Climate / Daniel T Potts -- Demoscopy and Demography / Josef Wieseh©œfer -- Peoples and Languages / Jan Tavernier -- Languages and Script / Adriano V Rossi -- Onomastics / R©ơdiger Schmitt -- The Inscriptions of the Achaemenids / Adriano V Rossi -- Elamite Sources / Matthew W Stolper -- Babylonian Sources / Michael Jursa -- Aramaic Sources / Holger Gzella -- Biblical Sources / Reinhard G Kratz -- Phoenician Sources / Josette Elayi -- Egyptian Sources / Gunter Vittmann -- Lydian, Carian, and Lycian Sources / Ivo Hajnal -- Greek and Latin Sources / Reinhold Bichler, Robert Rollinger -- Persia (including Kh¿±zest♯¹n) / R©♭my Boucharlat -- Media / Bruno Jacobs, David Stronach -- Babylonia and Assyria / Walter Kuntner, Sandra Heinsch -- Syria / Astrid Nunn -- Cyprus / Anna Cannav©ø -- Egypt / Melanie Wasmuth -- Asia Minor / Deniz Kaptan -- Caucasus Region / Florian S Knauss -- The Empire's Northeast / Claude Rapin -- The Empire's Southeast / Remy Boucharlat -- The Median Dilemma / Robert Rollinger -- Uraru / Mirjo Salvini -- From Assurbanipal to Cambyses / Robert Rollinger -- Elamite Traditions / Javier Alvarez-Mon -- The Great Conquests / Amelie Kuhrt -- Imperial Crisis / Gundula Schwinghammer -- The Establishment of the Achaemenid Empire / Robert Rollinger, Julian Degen -- From Darius II to Darius III / Carsten Binder -- The Conquest by Alexander / Krzysztof Nawotka -- Prsa and ¿®ja / Ali Mousavi, Touraj Daryaee -- Media / Bruno Jacobs -- Babylon / Robert Rollinger -- The Persian Gulf / Daniel T Potts -- The Arabian World / David F Graf, Arnulf Hausleiter -- Egypt / Joachim F Quack -- Nubia / Angelika Lohwasser -- The Cyrenaica / Andre Heller -- The Levant / Oskar Kaelin -- Asia Minor / Elspeth RM Dusinberre -- Cyprus and the Mediterranean / Andreas Mehl -- The Greek World / Mischa Meier -- Macedonia / Michael Zahrnt -- Thrace / Dilyana Boteva-Boyanova -- The Northern Black Sea / Gocha R Tsetskhladze -- The Caucasus Region / Wolfgang Messerschmidt -- The Nomads of the Steppes / Bruno Jacobs, Birgit Gufler -- The Iranian East / Seren Stark -- India / Kai Ruffing -- Roads and Communication / Wouter FM Henkelman, Bruno Jacobs -- The Interplay of Languages and Communication / Jean-Jacques Glassner -- Achaemenid Art - Art in the Achaemenid Empire / Bruno Jacobs -- Seals and Sealing / Mark B Garrison -- Royal Coinage / Matthias Hoernes -- Empire, Borders, and Ideology / Robert Rollinger -- Front Matter -- Satrapal Administration / Bruno Jacobs -- Hierarchy and ethno-classe dominante / Gian Pietro Basello -- Deportations / Josef Wiesehefer -- Persia / Wouter FM Henkelman -- Babylonia / Kristin Kleber -- Egypt / Damien Agut-Labordre -- Asia Minor / Christian Marek -- Bactria / Holger Gzella -- Taxes and Tributes / Johannes Hackl, Kai Ruffing -- Temple Economy / Cornelia Wunsch -- Babylonian Entrepreneurs / Caroline Waerzeggers -- The Residences / Bruno Jacobs -- The Court / Lloyd Llewellyn-Jones -- King - Elites and Subjects - Slaves / Gian Pietro Basello -- Banquet and Gift Exchange / Jacob L Wright, Meredith Elliott Hollman -- Clothes and Insignia / Wolfgang Messerschmidt -- Jurisdiction / Reinhard Pirngruber -- Diplomacy / Silke Knippschild -- Hunting and Leisure Activities / Eran Almagor -- Gender and Sex / Irene Madreiter, Kordula Schnegg -- Legitimization of War / Roel Konijnendijk -- Structure of the Army and Logistics / Christopher Hassan -- Military Organization and Equipment / Christopher Tuplin, Bruno Jacobs -- Mercenaries / Christopher Tuplin -- The Religion of the Achaemenid Rulers / Albert Jong -- The Achaemenids and the Avesta / Jean Kellens -- The Heartland Pantheon / Wouter FM Henkelman -- Practice of Worship in the Achaemenid Heartland / Wouter FM Henkelman -- Funerary Customs / Pierfrancesco Callieri -- Religions in the Empire / Manfred Hutter -- Schools, Erudition, and Wisdom / Lukasz Niesioowski-Span -- Astronomy and Astrology / John M Steele -- Persian "Enlightenment" / Sebastian Fink, Josef Wieseh©œfer -- Physicians and Medicine / Nils P Heeel -- Techniques of Art and Architecture / Alexander Nagel -- Statuary and Relief / Margaret Cool Root -- The Minor Arts / Mark B Garrison -- Poetry, Music, and Dance / Bruno Jacobs -- The Perspectives of Greek and Latin Sources / Reinhold Bichler -- "Perserie" / Margaret Miller, Stavros A Paspalas -- Jewish Perspectives on Persia / Erich S Gruen -- Perspectives in Europe in the Middle Ages and the Modern Era / Sabine Moeller -- Heirs of the Achaemenid Empire / Andreas Luther -- The Perception in Iran in the Medieval and Modern Era / Jan P Stronk -- Popular Culture and Its Traditions / Wolfgang Kofler, Robert Rollinger -- The Achaemenid Empire and Forgery / Rudiger Schmitt -- The Achaemenid Empire and Forgery / Ellen Rehm -- Western Europe / Julian Degen, Sean Manning -- The USA / Margaret Cool Root -- Eastern Europe / Muhammad Dandamayev -- Iran / Ali Mousavi -- The Achaemenid Empire / Josef Wieseh©œfer -- Names of Persons and Deities -- Topo- and Ethnonyms
Keywords: Achaemenid dynasty -- 559-330 B.C; Achaemenid dynasty; Achaemenid dynasty - 559-330 B.C; To 640; Iran -- History -- To 640; Iran -- Antiquities; Iran; Iran - Histoire - Jusqu'à 651; Iran - Antiquités